Exploring network relations between healthcare access and utilisation in individuals with rare diseases - Wehrli Susanne; Dwyer Andrew A; Matthias Baumgartner R; Landolt Markus A (Public Health in Practice)
Background: Rare diseases affect fewer than one in 2000 people and impact approximately 400 million individuals globally. High costs, uncoordinated care, and inadequate provider knowledge pose challenges to rare disease care. We aimed to examine the relationship between healthcare access and utilisation among rare disease patients in Switzerland. Study design: A cross-sectional survey was conducted with 314 individuals with a rare disease. Methods: Participants completed the Perception of Access to Healthcare Questionnaire (PAHQ) and provided data on healthcare utilisation (institutional and provider levels). Network analysis assessed nodes were based on expected influence (EI), predictability, and bridge centrality (BC). Results: Four PAHQ subscales (acceptability, availability, adequacy, and awareness) exhibited higher EI and predictability. Conversely, accessibility and affordability of healthcare services had lower EI and predictability scores. In terms of healthcare utilisation, hospitals, private practices, general practictioners (GPs), mental health professionals, and emergency services demonstrated elevated EI and predictability. Specialists and holistic healthcare providers exhibited lower EI and predictability. Affordability, disease course, as well as hospital, and GP utilisation had elevated BC values and emerged as key connectors between access and utilisation. Conclusion: This study illuminates the intricate dynamics of healthcare experiences for patients with rare diseases. This work validates network analysis as a valuable tool for examining healthcare systems. Findings can inform policies that address challenges faced by this vulnerable population, namely care integration for individuals with an unstable disease course.